The neonate was born with holoprosencephaly - reza saeidi; abdolhosein abasi (Mashhad University of Medical Sciences, 2014)
holoprosencephaly is a rare congenital brain malformation resulting from failure of diverticulation and cleavage of primitive prosencephalon which occurs at 4 - 8th week of gestation and is usually associated with multiple midline facial anomalies. it is the most common forebrain developmental anomaly in humans with prevalence of 1/16,000 in live borns, an incidence as high as 1:250 in conceptuses, and a worldwide distribution6. The etiology of HPE is very heterogeneous. First, this pathology can be caused by environmental or metabolic factors. The only formally recognized environmental factors are insulin-dependent diabetes mellitus (1% risk of HPE) and maternal alcoholism with a risk that cumulates with smoking . Clinical expression is variable, extending in unbroken sequence from a small brain with a single cerebral ventricle and cyclopia to clinically unaffected carriers in familial holoprosencephaly. Here. we report a boy 39 weeks neonatal case of holoprosencephaly with Antenatal ultrasonographic diagnosis, with microcephaly, hypotelorism, flat nose, a single nostril, a midline cleft lip and palate microcephaly.